Application of Diversion in Perspective Justice - Hermawan; Moh Nur Amin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The application of diversion from a justice perspective focuses on achieving case resolution that focuses more on recovery and rehabilitation, especially in cases involving children. In this context, diversion acts as an alternative to prevent children from formal criminal justice processes which tend to have negative impacts, such as stigmatization or trauma. Diversion is not just a transfer of case resolution, but is also part of a restorative justice approach. Thus, the application of diversion from a justice perspective is not only seen as a diversion from the legal process, but also as an effort to restore and provide opportunities for children to correct their mistakes, as well as reduce the negative impacts of involvement in the formal criminal justice system.